2020
DOI: 10.9758/cpn.2020.18.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Increases the Protective Effect of Citicoline on Aluminum Chloride-induced Cognitive Impairment

Abstract: Objective: Alzheimer's disease is a popular neurodegenerative disorder which is growing in the elderly people. Exposure to environmental pollutant like aluminum could trigger or accelerate its involved mechanisms like tau phosphorylation. The current study will evaluate the effect of alone or co-administration of Citicoline or/and magnesium on the aluminum chloride induced memory impairment. Methods: Male albino mice were randomly divided into different groups (n = 7). Memory impairment was induced via orally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
1
7
0
1
Order By: Relevance
“…Previous data represent that AlCl 3 -induced memory impairment is thought to be caused by a variety of ways 124 AlCl 3 cognitive toxicities have been linked to the upregulation of APP, Ab, NF-kB, AChE activity, nitric oxide release, oxidative stress, and the eventual neuronal apoptosis. 125 , 126 …”
Section: Resultsmentioning
confidence: 99%
“…Previous data represent that AlCl 3 -induced memory impairment is thought to be caused by a variety of ways 124 AlCl 3 cognitive toxicities have been linked to the upregulation of APP, Ab, NF-kB, AChE activity, nitric oxide release, oxidative stress, and the eventual neuronal apoptosis. 125 , 126 …”
Section: Resultsmentioning
confidence: 99%
“…This treatment reduced the apoptotic process by maintaining retinal ganglion cell and reducing the expression of vascular endothelial growth factor receptor-2 as well as glial fibrillary acidic protein (GFAP) [10], [28]. Another study showed that MgSO 4 has a protective effect on brain tissues of preeclampsia rat models by inhibiting signaling pathway of nuclear factor-κB (NF-κB)/intercellular adhesion molecule-1 [29] In rat models with cognitive disorders induced by aluminum chloride, the administration of MgSO 4 improved memory dysfunction [30]. Another study found that remifentanil or MgSO 4 when combined with sevoflurane produced adequate hypotensive anesthetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 90% of AD patients presented with BPSD, leading to independence reduction and incapability of completing daily activities. These might have impacts on medication adherence, tolerability and efficacy [ 35 ]. The overall adherence was 80.6% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of treating AD, BPSD is an important issue. BPSD lead to poor outcomes, distress among patients and caregivers, earlier placement in nursing homes, long-term hospitalization, misuse of medication, and increased health care costs [ 35 , 50 ]. Whether the oral solution benefits more than the conventional oral capsule in management of BPSD requires further evalua-tion.…”
Section: Discussionmentioning
confidence: 99%